KONDISI HOMOGENISASI DAN PRAPENINGKATAN SKALA PROSES MIKROENKAPSULASI MINYAK SAWIT - Tien R Muchtadi, Alfia Nurul Ilma, Dase Hunaefi, Sri Yuliani (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
Utilization of palm oil as downstream products is still remain limited. Palm oil contains high carotenoids ranging from 500 to 700 ppm. Carotenoids are very sensitive to heat and oxidation. Microencapsulation process conducted by two steps, i.e. homogenitation to produce emulsion and spray drying to produce microcapsule that protect its active compounds. Olein homogenization was the main process in the formation of an emulsion of palm oil prior to drying process. This process was influenced by speed, time and volume. Microcapsule formulation using maltodextrin, Arabic gum, and gelatin. The results showed that the process of homogenization affected the quality and characteristics of emulsion and microencapsulate of palm oil. An increase of volume and length of time did not significantly affect the characteristics of palm oil microcapsule, such as water content, solubility and water activity (p>0.05), but significantly affected the emulsion stability, surface oil, carotenoid contain and efficiency of microencapsulation (p<0.05) and also affecting the quality of microencapsulate (yield, water activity, solubility). Palm oil microencapsulation using spray dry could be applied at industrial scale. Keywords: carotene, homogenization, microencapsulation, palm oil, scale up